Moral Action and Professionalism - David W. Chambers (Journal of the California Dental Association)
Background As dentistry became a profession it crafted aspirational values to announce the highest standards for the relationship between individual practitioners and those who sought their care and of professional etiquette among colleagues. These standards evolved as dentistry underwent dramatic development in technique, scientific knowledge, commercial ownerships of practice, a shift toward insurance and the government paying for most of the dental bill, and an increasing voice for the public. Dentistry borrowed some of the principles from the bioethics movement in the 1970s and ‘80s.Objective Evidence is presented in this paper for six areas showing that measures of ethical impact such as public trust, disciplined licenses, teaching of ethics, and membership in organized dentistry suggest that further adjustments are needed to make the profession responsive to the current expectations of society and the profession itself.Conclusion An alternative to the descriptive lists of aspirational principles is presented. This involves two imperatives or expected types of behavior that close the gap between ideal images and typical behavior.Practical Highlights Moral action and professionalism (MAP) means not cheating, which is taking unjustified personal advantage of others, and being stewards of the common good that is the mark of a profession.